Effect of lung squeezing technique and reflex rolling on infants with acute respiratory distress syndrome - SHANMUGANANTH. E; REKHA. K; DIVYA LAXMI. P; PRIYANKA (International Journal of Pharma and Bio Sciences, 2017)
Acute respiratory distress syndrome is process of hypoxemic respiratory failure associated with pulmonary edema. Respiratory distress syndrome is the primary cause of neonatal mortality usually occurring in children of less than 36 weeks of gestation. Currently, in all hospital conventional chest physiotherapy is used as a supportive measure to treat infant with Respiratory distress syndrome. Twenty participants were recruited in a consecutive manner and allocated in two groups through odd even method Group A treated with Lung squeezing technique and conventional physiotherapy, Group B treated with reflex rolling along with conventional physiotherapy. All participants recruited through physician reference and screening according to selection criteria. Outcomes included was respiratory rate and oxygen saturation they were tested at baseline as a Pre test and post test measurements were taken after the treatment duration of 5 days. Demographic data were analyzed through statistical package for social science. Statistical analysis used was descriptive analysis to find mean and standard deviation. Both lung squeezing and reflex rolling technique were effective in reducing RR and improving SpO2. Anyhow while comparing mean difference reflex rolling shows more improvement than lung squeezing technique.